Hair Maintenance and Chemical Hair Product Usage as Barriers to Physical Activity in Childhood and Adulthood among African American Women - Gaston, Symielle A. (Int J Environ Res Public Health, 2020)
Qualitative studies have identified haircare practices as important culturally specific barriers to physical activity (PA) among Black/African American (AA) women, but quantitative investigations are lacking. Using the Study of Environment, Lifestyle and Fibroids data among 1558 Black/AA women, we investigated associations between hair product usage/hair maintenance behaviors and PA during childhood and adulthood. Participants reported childhood and current chemical relaxer and leave-in conditioner use. Self-reported PA included childhood recreational sports participation, leisure-time PA engagement during adulthood, and, at each life stage, minutes of and intensity of PA. Adjusting for socioeconomic and health characteristics, we used Poisson regression with robust variance to estimate prevalence ratios (PRs) and 95% confidence intervals (CIs) for each PA measure for more vs. less frequent hair product use/hair maintenance. Thirty-four percent reported ≥twice/year chemical relaxer use and 22% reported ≥once/week leave-in conditioner use at age 10 years, and neither were associated with PA at age 10 years. In adulthood, ≥twice/year chemical relaxer users (30%) were less likely (PR = 0.90 [95% CI: 0.79–1.02]) and ≥once/week leave-in conditioner users (24%) were more likely (PR = 1.09 [95% CI: 0.99–1.20]) to report intense PA compared to counterparts reporting rarely/never use. Hair product use/maintenance may influence PA among Black/AA women and impact cardiometabolic health disparities.